Thyroid hormone status interferes with estrogen target gene expression in breast cancer samples in menopausal women - Conde, Sandro José [UNESP]; Luvizotto, Renata de Azevedo Melo [UNESP]; Síbio, Maria Teresa de [UNESP]; Nogueira, Célia Regina [UNESP] (Isrn Endocrinology, 2014)
We investigated thyroid hormone levels in menopausal BrC patients and verified the action of triiodothyronine on genes regulated by estrogen and by triiodothyronine itself in BrC tissues. We selected 15 postmenopausal BrC patients and a control group of 18 postmenopausal women without BrC. We measured serum TPO-AB, TSH, FT4, and estradiol, before and after surgery, and used immunohistochemistry to examine estrogen and progesterone receptors. BrC primary tissue cultures received the following treatments: ethanol, triiodothyronine, triiodothyronine plus 4-hydroxytamoxifen, 4-hydroxytamoxifen, estrogen, or estrogen plus 4-hydroxytamoxifen. Genes regulated by estrogen (TGFA, TGFB1, and PGR) and by triiodothyronine (TNFRSF9, BMP-6, and THRA) in vitro were evaluated. TSH levels in BrC patients did not differ from those of the control group (1.34 ± 0.60 versus 2.41 ± 1.10  μ U/mL), but FT4 levels of BrC patients were statistically higher than controls (1.78 ± 0.20 versus 0.95 ± 0.16 ng/dL). TGFA was upregulated and downregulated after estrogen and triiodothyronine treatment, respectively. Triiodothyronine increased PGR expression; however 4-hydroxytamoxifen did not block triiodothyronine action on PGR expression. 4-Hydroxytamoxifen, alone or associated with triiodothyronine, modulated gene expression of TNFRSF9, BMP-6, and THRA, similar to triiodothyronine treatment. Thus, our work highlights the importance of thyroid hormone status evaluation and its ability to interfere with estrogen target gene expression in BrC samples in menopausal women.